(untitled) (Sciences & Technology. A, exactes sciences, 2004)
In the present work, some mechanical properties of chromium carbides coating on steel substrates were studied. The samples were prepared by d.c. magnetron sputtering of a pure Chromium (Cr) layer on steel substrates containing 1%wt of Carbon. The system (substrate/coating) was then annealed in vacuum at a temperature at which the carbon of the substrate may diffuse into the Cr metallic film. This fact leads to the formation of chromium carbides, which are identified by X-ray diffraction as Cr7C3, Cr23C6 and (Cr,Fe)7C3. The study by nanoindentation shows that the microhardness decreases with increasing of annealing temperature until 800°C, then increases rapidly to reach a maximum (≈2800 Kg.mm-2) at 1000°C. The internal stresses, measured by X-ray diffraction, are compressive at 900°C and tensile at 1000°C in the chromium coating. Nevertheless, they are tensile in the substrates regardless the temperature. The sign change of the stresses in the coating is probably due to the phase transformation (Cr7C3→(Cr,Fe)7C3)).